Research on the Impact of Family Environment and Counselling on Occupational Aspiration of Class 11 Students: Examining the Influence of Family Environment and School Climate on Students' Career Aspirations (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present research was conducted with the intention of examining the educational expectations of secondary school students in relation to their school environment and of defining the discrepancy between the educational expectations and the school environment of secondary school students on the basis of their locality. The school atmosphere is almost as critical as the home environment. Parental preferences and the complexities of social relationships have developed as central influences in educational ambitions. The school climate shapes the actions of the infant. Therefore, the relationship of children with friends or peers almost often has an effect on the whole world that affects them. The definitions of technical ambitions and job goals are very similar. On the basis of the study, the Career Counselor will guide the student towards a particular career, suggesting possible alternatives and options.